Philadelphia's been good to me [compact disc] - Vile, Kurt (Verve Records, 2026)
Kurt Vile's album captures his deep affection for Philadelphia, the city where he lives and records most of his work. The collection highlights his signature jangly guitar sound, expansive instrumental moments, and songwriting that balances playful humor with heartfelt sentiment, reflecting both the spirit of the city and his personal connection to it.